Modifikasi membran polyvinylidene fluoride (PVDF) dengan penambahan polyvinyl pyrrolidone (PVP) dan kitosan dengan metode inversi fasa - Muhfadzallah Muhfadzallah; Umi Fathanah; Sri Aprilia; Syawaliah Muchtar; Mukramah Yusuf (Institution for Industrial Research and Standardization of Industry - Padang, 2022)
One of the simplest approaches to improve membrane performance is to increase the hydrophilicity of the membrane. This article describes the manufacture of activated polyvinylidene fluoride (PVDF) based membranes using PVP and chitosan as organic additives, with the specific aim of increasing the hydrophilicity of the membranes. Variations of dope solution were made by adding 1% by weight of PVP and 1, 2, and 3% by weight of chitosan into three different PVDF polymer solutions. The effect of additives on the membrane was obtained by evaluating chemical functional groups by ATR-FTIR, morphological changes by SEM, and filtration performance. SEM images show that the presence of additives changes the morphological structure of the membrane. This change also had a significant impact on the membrane performance, as evidenced by the increased permeability of the pure water solution and the removal of dissolved humic acid. Overall, modified PVDF membranes with 1% by weight of PVP and 1, 2, and 3% by weight of chitosan resulted in much better permeability than unmodified PVDF membranes due to their excellent hydrophilicity.